Acute pancreatitis due to severe hypertriglyceridemia in the COVID-19 era: The role of therapeutic plasma exchange. (February 2022) - Pavanello, Francesca; Colpo, Anna; Tison, Tiziana; Fabris, Roberto; De Silvestro, Giustina; Marson, Piero
Abstract: The psychosocial consequences of the COVID-19 pandemic caused multifaceted challenges in clinical and therapeutic practices. This was the case at the Therapeutic Apheresis Unit of the Padua University Hospital too. Several published reports describe the increase in alcohol and food addiction diseases. In this context, during the last months, the Padua Therapeutic Apheresis Unit treated many more patients with acute pancreatitis due to severe hypertriglyceridemia with therapeutic plasma exchange than in the previous ten years. Furthermore, retrospective cohort studies have been recently published describing the onset of acute pancreatitis during the COVID-19 infection even if, to date, there is still insufficient evidence to estabilish a direct causality. Anyway, the COVID-19 pandemic translated into changes of the overall disease prevalence scenario and therefore the Padua Therapeutic Apheresis Unit will need to reorganise its Therapeutic Apheresis activity.